Variability in bael (Aegle marmelos Correa) germplam collected from Rajasthan (Indian Journal of Arid Horticulture, 2025)
Bael (Aegle marmelos Correa.) is a nutritive and medicinally important drought hardy fruit tree found throughout the country. Its fruit is eaten as fresh and also used for making several value added products. A survey for biodiversity of bael was conducted in Chomu, Jaipur, Sariska area of Alwar district during April-May,2014 to identify elite type germplasm having better horticultural traits. Twelve fruit samples from different location were collected for physical and biochemical analysis. Seedlings of different age groups were available on the farmer's field. However, in Sariska forest naturally grown bael trees having very small size fruits of inferior quality were observed. Variability in fruit shape- oval to cylindrical, round, fruit weight from 0.580kg to 1.860kg, number of fruit 21-130 per tree was observed. The pulp colour light yellow to dark yellow and TSS ranged from 22.4 to 40.6°brix. Out of these, four plus tree (Bael accession, 4, 6, 10 and 12) were marked having superior bearing habit, medium fruit size and better fruit quality in respect of pulp colour, taste, high TSS (brix) content and low acidity (0.22%) for further study.
Keywords: Bael; Aegle marmelos; variability; germplasm; Sariska forest; Rajasthan